ANALISIS PIUTANG TERHADAP LIKUIDITAS PERUSAHAAN (Studi Kasus pada PT. Telekomunikasi Indonesia Tbk. dan PT. Indosat Tbk.) - Wihananto, Adri (Jurnal Ilmiah Binaniaga, 2012)
As according to section 3 association of company, PT csope. Single Telecommunications of especial Tbk Activity and especial activity scope of company is to carry out domestic telecommunications sevice, which cover telephone, telex, telegram, satellite, customer circuit, electronic letter and peripatetic communications service and cellular, In order to quickening telecominications medium development and make Company as operator have internastional level to, and also improve technology, membership and knowledge all its employees, in the year 1995. Company have work is equal to all partner in development, and management pengoprasian of telecommunications medium in five from seven regional division through is same job pattern of Operation (“KSO”)As according to section 3 Assocition of Company, especial activity and scope activity of PT. Indosat Tbk cover to make a move in the field of multimedia and telecommunications in Indonesia give amenity to all its customer for the case of question in around telecommunications (seluler, SLI, etc), denunciating, guidance subscribe to, purchasing of maiden card of GSM prabayar/ CDMA/ internet prabayar card/ refill voucer, and/ or payment of invoice, direct etc in place. PT. Telecomunications Indonesia Tbk and PT. Indosat Tbk conduct sale creditly as a mean to improve sale volume, because at the higtht of sale volume hence directly can improve provite. Credit sales will result the happening of receivable, the duration receivable turn into cash in company can be measured with receivable turn overratio and period gathering of receivable. Receivable turn over And period gathering of tardy receivable can influence company likuiditas storey; accepted Excelsior credit sales, hence progressively lower company likuiditas storey; level conversely progressively lower accepted credit sales, hence excelsior mount company likuiditasTo measure or analyse credit sales storey; level used by formula which consist of : receivable turn over ratio, and period ratio gathering of receivable. While to mesure company likuiditass storey; level used by likuiditas ratio, that is : ratio current/ fluent ratio, ratio quick/ ratio quicly, and ratio cash/ cash ratio. Storey level Sale of PT. High Telecomuniations Indonesia Tbk enough with good company likuiditas level of fluent ratio, ratio quickly and cash ratio under 100% indicating that company find difficulties finance in fulfilling obligation short-range or fluent debt on time. While at PT. Indosat Tbk, mount from high sale enough, with level mount good company likuiditas of fluent ratio, ratio quickliy and cash ratio below/ under 100 % indicating that company find difficulties finance in fulfilling obligation short-range or fluent debt on time.Keywords: accounts receivable, the company's liquidity.